Activation of a MnO2 cathode by water-stimulated Mg2+ insertion for a magnesium ion battery1. Issue 7 (21st February 2015) - Song, Jaehee; Noked, Malakhi; Gillette, Eleanor; Duay, Jonathon; Rubloff, Gary; Lee, Sang Bok
<x xml:space="preserve">Abstract</x> We demonstrate that MnO2 nanowire electrode is "activated" for efficient Mg2+ insertion/deinsertion by introducing water molecules in to the electrolyte.